Lernen und kommunikatives handeln im zeitalter des internet - Westphal, Werner (Journal of Business Economics and Management, 2003)
The present paper focuses on different aspects of e‐learning. Differences between traditional learning processes on the basis of written texts and e‐learning on the basis of hypertext are discussed in this context. The main differences are to be found in the way of transportation and reception and the kind of presentation of information (multi‐medial). This, of course, has a lot of consequences for both people's socialization and the teaching process itself. Young people in particular need help to find effective ways of using the new possibilities of information transfer. Support should be provided by specially qualified tutors. One of the important conclusions is that e‐learning is a new challenge for studies in different fields as well as a challenge and chance for interdisciplinary cooperation.Article in German.First Published Online: 14 Oct 2010